Measuring the perception of Malaysian SME towards e-commerce as an innovation / Juliana Hamka Kamaroddin, Dianne Cheong Lee Mei and Azlin Ahmad - Kamaroddin, Juliana Hamka; Cheong, Dianne Lee Mei; Ahmad, Azlin (Research Management Institute (RMI), 2008)
This paper presents a quantitative study in measuring the perception of Malaysian SME towards ecommerce as an innovation and factors affecting the adoption of it. It is concerned with initiatives that are intended to help SME in Malaysia to adopt E-commerce as an innovation. The research has two main emphases: First, it presents some preliminary findings on the perception of Malaysian SME towards E-commerce as an innovation; and the level of confidence towards E-commerce as an innovation. Second, it streamlines various initiatives by Ministry of International Trade and Industry (MITI), Small and Medium Industries Development Corporation (SMIDEC), BankNegara Malaysia and local governments in accelerating the acceptance of E-commerce by Malaysian SME. The study engaged 38 SME participants through a survey using a self-administered questionnaire. 32% of the surveyed SME are from the Type 1 Industry; comprising manufacturing, manufacturing related services, and agro-based services and about 68% are from Type 2 Industry comprising services, primary agriculture, and ICT. The self administered questionnaire consists of two sections. Section I contains demographic information and SME specification while Section II contains 37 items: 31 items utilised Likert Scales items ranging from 1 (strongly disagree) to 5(strongly agree), and six items utilised defined interval scales. Rogers' attributes of innovations (2003): relative advantage, compatibility, complexity, trial ability and observability were used in the construct of the research instrument. This research emphasizes on Rogers'framework, as it was found useful where the study sought to understand the diffusion and use of Ecommerce by Malaysian SME in the investigation. Descriptive statistics were used to analyse and present empirical data of the 38 SME. The results from the quantitative data provided information on addressing barriers to SME, and confirmed the characteristics of Rogers' adoption categories. The study shows that the instrument which was designed with seven constructs lacked internal consistency in two determinants: relative advantage and observability. Findings interpreted through Rogers' theory suggest that an action plan should include initiatives to help SME towards E-commerce as an innovation.